P239 Low prevalence of extra-thoracic airway hyper-responsiveness in UK patients with chronic refractory cough. (12th November 2015) - Menon, A; Hull, J; Chung, KF; Usmani, O; Ward, S
Abstract : Introduction: Prior research indicates that chronic refractory cough (CRC) is associated with a high prevalence of extra-thoracic airway hyper-responsiveness (EAHR). 1 This heightened laryngoconstrictor reflex can be characterised using standard bronchoprovocation tests (e.g. histamine or hypertonic saline); whereby attenuation in the inspiratory component of the flow-volume curve is evaluated in response to escalating doses of the stimulus. Aims and objectives: To determine the prevalence of EAHR in a cohort of CRC patients in the UK undergoing cough assessment, and to relate EAHR to other disease characteristics. Methods: Data was retrospectively evaluated for all CRC patients completing cough assessment with histamine bronchoprovocation challenge, between 2013 and 2015. EAHR was defined by a 25% dose-responsive fall in the mid-inspiratory flow (PC25FIF50) in response to ≤ 8 mg/ml histamine. 2 EAHR data was compared with other simultaneous investigation results, including overnight pH/impedance results and co-existing nasal disease. Results: We studied 57 adult CRC patients (n = 42, female; 74%), mean ±SD age 54.6 ± 12.4 years, BMI 28.2 ± 5.9 kg/m 2, reporting a duration of cough 5.5 years (0.8–50) with a median cough VAS score of 57 (16–90). The majority of patients (56%) reported cough without other respiratory symptoms, whereas 12 (21%) reported cough with dyspnoea and wheeze. Evidence of EAHR was found in three patients (5.3%). At a reduced cut-off (PC20FIF50 ≤ 16 mg/ml) the prevalence of EAHR was greater (12%) (Figure 1 ). Patients with a positive EAHR test at this cut-off were younger (p < 0.01, mean age 44 yrs versus 56 yrs) and more likely to report respiratory dyspnoea and wheeze (p < 0.05). In patients completing an overnight reflux study (n = 52), 32 (62%) had evidence of reflux. 21 (37%) patients had co-existing nasal disease. However, presence of reflux or nasal disease was not predictive of EAHR (both p > 0.05). Conclusion: EAHR was not prevalent in CRC patients, completing assessment at a specialist cough service, when using a standard histamine bronchoprovocation test. Differences from prior published data may be explained by methodological differences, specifically the application of stringent control of the measures of reproducibility of inspiratory flow parameters and dose response criteria. References: 1 Bucca C, Rolla G, Scappaticci E, et al . Histamine hyperresponsiveness of the extrathoracic airway in patients with asthmatic symptoms. Allergy 1991;46 :147–53 2 Bucca C, Bugiani M, Culla B, et al . Chronic cough and irritable larynx. J Allergy Clin Immunol . 2011;127 :412–9